Análise numérica de pilares de aço com restrições axial e rotacional em situação de incêndio - Bubach, Caroline Rainha (2016)
The performance of a steel column in fire is highly influenced by its interaction with the beams, slabs and columns of the surrounding structure, because the different thermal strains developed between the heating elements and the elements that remain relatively cold develop axial and rotational restraints in the column that modify its critical temperature and fire resistance. Studies of the influence of axial and rotational restraints on the fire resistance of steel columns are recent and most of the research carried out only considered the influence of axial restraint, without taking into account the rotational restraint. This study aims to analyze the behavior of I section steel columns in fire with axial and rotational restraint, in isolation and acting simultaneously. The influence of the slenderness of the column, the load level and axial and rotational restraint ratio were analyzed numerically using the finite element program ANSYS v17.0. The main results were that the two restraints, the axial and rotational, have opposite effects on the fire resistance of the columns and the larger the load level and slenderness, lower fire resistance. The critical times and critical temperature values numerically obtained were compared with the formulation of the ABNT NBR 14323: 2013.